Debate: Strategically Working in Parallel to Traffickers - Tournecuillert, Vincent (Anti-Trafficking Review, 2014)
Let’s be realistic, counter-trafficking teams will never be as effective as the proactive and flexible networks of outlaws that violate the rights of millions of people each year. The ‘bad guys’ operate without the same financial limitations such as bureaucratic red tape and donor criteria, and take advantage of patchy and often uncoordinated border surveillance that is chronically untrained in detecting trafficking in persons. Non-governmental organisations (NGOs) involved in the fight against human trafficking—and in direct contact with presumed victims (their status is not assessed until at a stage later than this initial contact)—are in a diametrically opposite situation. They must carefully abide by the national and international legal frameworks that their criminal antagonists ignore. Donors and national authorities operate within the constraints of geographic target areas and funding cycles. Since counter-trafficking actors neither create the markets nor devise the routes for trafficking, their strategic cross-border (or long distance) partnerships are always a few steps behind the traffickers, if not many steps behind, and rarely efficient.